Effects of peritoneal-and hemodialysis on levels of plasma protein and lipid oxidation markers in diabetic patients - Sozer, V.; Guntas, G. Korkmaz; Konukoglu, D.; Dervisoglu, E.; Gelisgen, R.; Tabak, O.; Kalender, B.; Uzun, H. (EDIZIONI MINERVA MEDICA, 2013)
Aim. The aim of this paper was to evaluate the effects of dialysis procedures on oxidative stress in diabetic patients. Methods. The study was performed on 15 nondiabetic hemodialysis (HD) patients, 30 nondiabetic perinoteal dialysis (PD) patients, 18 diabetic HD patients (DHD), 15 diabetic PD patients (DPD), and 20 healthy controls. Plasma thiobarbituric acid reactive substances (TSARS), protein carbonyl (PCO), and oxidized LDL (oxLDL) were determined as oxidative stress markers. Plasma thiol (P-SH), erythrocyte glutathione (GSH) levels, and serum paraoxonase (PON1) activities were measured as antioxidants. Results. HD patients have significantly higher oxLDL, TBARS and PCO levels and significantly lower P-SH levels than PD patients. DHD patients have significantly higher PCO levels and PON1 activities and significantly lower GSH levels than non-diabetic HD patients. There was no any difference in oxidative stress parameters between DPD and nondiabetic PD patients. Conclusion. Oxidative stress is exacerbated by HD in diabetic patients. Treatment strategy with antioxidants in dialysis patients may be associated with a worsened survival.
Keywords: Peritoneal dialysis; Renal dialysis; Oxidative stress; Diabetes mellitus; Kidney failure, chronic; HIGH-DENSITY-LIPOPROTEIN; CARDIOVASCULAR-DISEASE; DIALYSIS PATIENTS; NITRIC-OXIDE; RISK-FACTORS; STRESS; PARAOXONASE; MORTALITY; General & Internal Medicine